Asymptomatic marginal zone lymphoma detected on routine mammogram, an unusual presentation - Green, Ryan J.; Vennam, Sarath; Ireland, Max; Withey, Grant; Melloy, Amelia (International Surgery Journal, 2024)
A patient in her 60 years presented for routine mammographic screening. A lesion was identified, which on biopsy was proven to be marginal zone lymphoma (MZL). MZL is a group of indolent non-Hodgkin’s B-Cell lymphomas. Involvement of breast tissue is rare and can mimic more common breast pathology. In addition, the patient had widespread subcutaneous lesions which is also atypical of the cutaneous form of MZL lymphoma. This case describes the multi-modality radiological findings of this uncommon presentation of diffuse cutaneous MZL.